Cooking a nation of consumers: Peru as global brand - Matta Aguirre, Raúl (2012)
Nation branding or “marca país” programs are intended to articulate a new and positive image for external consumptionand, at the same time, to revive national pride. This article adopts a critical interpretive approach and analyses thesymbolism in the TV spot of Peru's nation branding campaign. The analysis points out tensions and contradictions in theadvertisement to generate insights about symbolic commodification in a context of economic growth, after decades of economicdecline and political incertitude. The findings state that the campaign appropriates national identity for the purposes ofneoliberal globalization. This appropriation constrains national imaginaries within an ahistorical, depoliticized frame,resulting in an image gallery in where old and new stereotypes intend to live together. In this way, nation branding also servesto foreclose democratic ways for national redefinition.